Methods of financing waqf development in Singapore = أساليب تمويل تطوير األوقاف في سنغافورة - Nasar, Ashraf Jomah Mohammed; Saleh, Abdulmajid Obaid Hasan; Alhajri, Falah M F SM; El Amrani, Taoufiq (EuroMid Academy of Business & Technology (EMABT), 2020)
The Waqf sector in the Muslim world suffers in general from a state of negligence, and a lack of tactics and strategies in taking advantage of it, which results from cumulative and overlapping factors. This phenomenon invites for an investigation of successful Waqf experiences around the world, of which Singapore is the pioneer in it. The Waqf experience in Singapore is considered one of the most successful experiments at the Muslim world level, both in terms of the organization, and the investment. The sector has witnessed a remarkable development as effective modern methods and techniques were discovered. The study aims to reveal the reality of this experience, which includes the following Waqf funds: funds for mosques, funds for the handicapped, Quran memorization, as well as education, scientific research, innovation and others. However, the monetary Waqf has gained popularity in the sector, unlike the Waqf of immovable assets. Muslims in Singapore have realized the importance of the monetary Waqf and its role in collecting social savings, converting them into social capital, and developing the social capital market; to stimulate the merging between social security and social care, and to achieve the legitimate objectives of the Waqf and public interests. The Waqf administration in Singapore has used Sukuk to develop some of its endowments (Waqfs), therefore, the study will address how the Waqf in Singapore has benefited from this method in financing the development of endowments in both the construction project of a building on Beach Road 11, and a project to raise $ 35 million for the project to develop Waqf assets on Street Bencoolen. The researcher has employed both a case study as well as a descriptive analytical approach.